MENGUNGKAP PERSEPSI WAJIB PAJAK ATAS PENDAMPINGAN RELAWAN PAJAK - I Nyoman Putra Yasa; Ni Made Ayu Sri Putri Artini; Luh Melly Astari; Ni Putu Purnama Sari (Universitas Bunda Mulia, 2021)
ABSTRACT: The purpose of this research to explore the perceptions of taxpayers on the satisfaction of assistance performed by tax volunteers at the Tax Volunteer placement location. There are 4 (four) locations for the placement of Tax Volunteers, namely KPP Pratama Singaraja, KP2KP Negara, KP2KP Amlapura and Tax Center Undiksha. This research use desciptive qualitative approach. The sampling technique used in this research was purposive sampling with interview techniques in collecting research data. The population in this research are taxpayers who carry out the duty to annual tax return through e-Filing. Meanwhile, the sample in this research were taxpayers whose reporting the annual tax return were assisted by Tax Volunteers in the 4 (four) placements. The results of this research indicate that taxpayer assistance activities by tax volunteers in helping to fill individual annual tax returns are very effective. This can be seen from the satisfaction of taxpayers after receiving assistance by Tax Volunteers. Taxpayers are satisfied with the assistance of tax volunteers because the annual tax return reporting process is easier, faster and Tax Volunteers are able to guide Taxpayers in filling out their own. This assistance helps reduce the difficulties experienced by Taxpayers in understanding SPT filling independently. Taxpayer satisfaction is expected to increase compliance in reporting the Annual Tax Return. The sustainability of the Tax Volunteer program is also highly expected because it is considered very effective for taxpayers who do not understand the procedures for submitting annual tax return, especially those who are not yet competent with technological advances.Keywords: Perception, Assistance, e-Filing, Tax Volunteers ABSTRAK: Penelitian ini bertujuan untuk menggali persepsi wajib pajak atas kepuasan pendampingan yang dilakukan oleh Relawan Pajak di lokasi penempatan relawan pajak. Adapun 4 (empat) lokasi penempatan Relawan Pajak yaitu KPP Pratama Singaraja, KP2KP Negara, KP2KP Amlapura dan Tax Center Undiksha. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Teknik penentuan sampel yang digunakan dalam penelitian ini adalah purposive sampling dengan teknik wawancara dalam pengumpulan data penelitian. Yang menjadi populasi dalam penelitian ini adalah Wajib Pajak yang melaksanakan kewajiban dalam melaporkan SPT Tahunan melalui E-Filing. Sedangkan, sampel dalam penelitian ini yakni Wajib Pajak yang kegiatan pelaporan SPT Tahunannya didampingi oleh Relawan Pajak di 4 (empat) penempatan tersebut. Hasil penelitian ini menunjukan bahwa kegiatan pendampingan wajib pajak oleh relawan pajak dalam membantu pengisian SPT tahunan orang pribadi sangat efektif. Hal ini dapat dilihat dari kepuasan wajib pajak setelah mendapatkan pendampingan oleh relawan pajak. Wajib Pajak puas atas pendampingan relawan pajak dikarenakan proses pelaporan SPT Tahunan menjadi lebih mudah, cepat dan para relawan pajak mampu menuntun wajib pajak dalam pengisian SPT-nya. Pendampingan ini membantu mengurangi kesulitan yang dialami Wajib Pajak dalam memahami pengisian SPT secara mandiri. Kepuasan Wajib Pajak diharapkan mampu meningkatkan kepatuhan dalam pelaporan SPT Tahunan. Keberlanjutan program relawan pajak juga sangat diharapkan karena dinilai sangat efektif bagi wajib pajak yang belum mengerti tata cara penyampaian SPT khususnya yang belum cakap akan kemajuan teknologi.Kata kunci: Persepsi, Pendampingan, E-Filing, Relawan Pajak